Proceedings of the 10th ACM Symposium on Information, Computer and Communications Security 2015
DOI: 10.1145/2714576.2714617
|View full text |Cite
|
Sign up to set email alerts
|

Message Integrity Protection over Wireless Channel by Countering Signal Cancellation

Abstract: Physical layer message integrity protection and authentication by countering signal-cancellation has been shown as a promising alternative to traditional pure cryptographic message authentication protocols, due to the non-necessity of neither pre-shared secrets nor secure channels. However, the security of such an approach remained an open problem due to the lack of systematic security modeling and quantitative analysis. In this paper, we first establish a novel correlated jamming framework to study the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The vulnerability of preliminary orthogonal blinding results from the unchanged main channel, which allows the eavesdropper to estimate it via known symbols and filter the AN out. Actually, this flaw can be amended with the channel randomization approach, which is to actively randomize the wireless channel by introducing special antennas [21], [24], antenna motions [22] or artificial channel disturbance [23]. Intuitively, when the wireless channel is rapidly randomized, Eve can be blocked from gathering enough symbols for filter training.…”
Section: Robin: Channel-randomized Orthogonal Blindingmentioning
confidence: 99%
See 1 more Smart Citation
“…The vulnerability of preliminary orthogonal blinding results from the unchanged main channel, which allows the eavesdropper to estimate it via known symbols and filter the AN out. Actually, this flaw can be amended with the channel randomization approach, which is to actively randomize the wireless channel by introducing special antennas [21], [24], antenna motions [22] or artificial channel disturbance [23]. Intuitively, when the wireless channel is rapidly randomized, Eve can be blocked from gathering enough symbols for filter training.…”
Section: Robin: Channel-randomized Orthogonal Blindingmentioning
confidence: 99%
“…Different from this work, their scheme is only applicable to single-antenna transmitters and does not use pre-coding. To defend against active man-in-the-middle attacks, Hou et al [23] and Pan et al [24] randomized the wireless channel with a fan and a reconfigurable antenna respectively to prevent online signal cancellation. All these works show that channel randomization approach can be a powerful tool to enhance physical-layer security.…”
Section: Introductionmentioning
confidence: 99%
“…However, OOB channels usually require non-trivial human support and advanced user interfaces. To reduce the human interaction there have been few past attempts to design in-band message integrity protection mechanisms, which assume that signal cancellation over the wireless channel is not possible [5], or occurs with bounded success [7], [23]. For example, the Tamper-Evident Pairing (TEP) protocol proposed by Gollakota et al [8], and the integrity codes (I-codes) proposed byČapkun et al [5] both assumed the infeasibility of signal cancellation.…”
Section: Related Workmentioning
confidence: 99%
“…However, the infeasibility of signal cancellation assumption does not always hold. Pöpper et al first showed the feasibility of signal cancellation attacks using carefully placed relay nodes and directional antennas [22], Recently, Hou et al [23] showed that success probability of signal cancellation attack in the oneto-one setting depends on the randomness of the legitimate channel. A typical indoor environment may not be sufficient because the devices are static and the channel is usually stable.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation